Separation of Maternal and Newborn Care in US Hospitals: A Systemic Threat to Survival, Health and Well-Being - Kavya I. Anjur; Gary L. Darmstadt (Taylor & Francis Group, 2023)
ABSTRACTThrough greater understanding of past social, cultural, economic, political, scientific and technological forces which shaped our current health systems to separate mothers and newborn infants, we can begin to devise effective approaches to reshape these systems to meet the needs of mothers and newborn infants today. Medical science and technology have evolved vastly in the last century; however, effects of historical factors persist in our current health care systems, reflected in separate maternal and neonatal care in different departments with distinct guidelines, providers, and treatment locations. This separation prevents maternal-infant skin-to-skin contact and bonding, which significantly affects infant development, well-being, and that of their caregivers. We explore historical precedents for the separation of maternal-newborn care, including the transition from midwifery home care to hospital obstetric care, reasons for the increase in hospital births and hospital nursery development, and the effects of world wars, federal acts, health insurance, rooming-in practices, and the development of medical advances such as antibiotics, on hospital infrastructure. This information is evaluated in the context of modern scientific advancements to show that the conditions which shaped health systems to separate mothers and newborns in the past no longer hold. The insights gained will help to identify strategic actions to reshape health care systems to enable more integrated maternal-newborn care and the practice of Kangaroo Mother Care, and to improve survival outcomes and well-being for mothers, families, and their newborn infants.